THE VALIDITY AND RELIABILITY STUDY OF THE SCALE OF MORAL DISENGAGEMENT (Third Sector Social Economic Review, 2019)
The purpose of this study was to adapt Moral Disengagement Scale developed by Moore et al. (2012) into Turkish. Four different studies were conducted to test the validity and reliability of the scale of moral disengagement. In order to examine the linguistic equivalence of the scale, English-Turkish and Turkish-English versions of the scale were applied in two different samples and a significant and positive relationship was found between the two versions. In order to examine the construct validity of moral disengagement, explanatory and confirmatory factor analysis was performed in two different samples. The results showed that the Turkish version of the moral disengagement scale had a single-factor structure as in the original one and that this single-factor structure had good fit indices. Correlation analysis for the criterion-based validity of the scale showed significant results. Moreover, in the last study for the reliability of the moral disengagement scale, test-retest, cronbach’s alpha reliability coefficient and split-half methods were examined in different samples. These results indicated that the Turkish version of the moral disengagement scale is a valid and reliable scale.
Keywords: Moral disengagement scale; adaptation; validity; reliability